UPAYA MENINGKATKAN KETERAMPILAN SOSIAL SISWA MELALUI LAYANAN BIMBINGAN KELOMPOK DENGAN TEKNIK ROLE PLAYING KELAS VII DI SMP NEGERI 7 MUARO JAMBI - Amelia, Resni; Tanjung, Yanto; Susanti, Desy (STKIP Subang, 2026)
This research stems from the reality that students at SMP Negeri 7 Muaro Jambi frequently encounter difficulties in social skills. Students often fail to communicate effectively, feel uncertain when interacting with others, and struggle to cooperate with classmates. Social skills play a crucial role in adolescent development as they help children form positive relationships with others. This study aims to improve students' social skills through group guidance services using role-playing techniques. The research method employed is action service research conducted in three cycles, with each cycle consisting of two meetings. The subjects of this study were 7th-grade students at SMP Negeri 7 Muaro Jambi who obtained low scores on the social skills pre-test questionnaire. Data collection methods involved participant observation, questionnaires, and interviews with students, guidance counselors, and homeroom teachers. The results of this study indicate that the use of role-playing techniques in group guidance significantly helps students improve their social skills. Students were able to practice adjusting their behavior to social situations, learn to empathize with others' feelings, and receive direct feedback from group members. A clear difference was observed when comparing the average pre-cycle score of 43% to 85% in the third cycle. This study demonstrates that the use of group guidance with role-playing techniques is an effective way to help students enhance their social skills within the school environment.